Bioenergy for Stress Relief in University Students: A Randomized Controlled Trial. Issue 1 (2nd January 2022) - Running, Alice; Hildreth, Laura; John-Henderson, Neha
ABSTRACT: This study addressed the efficacy of a 20-minute Chakra Connection to treat self-assessed stress in a group of university students. A randomized, control design was used to identify group mean differences for intervention and control groups. A convenience sample of university students was randomly assigned to an intervention (Healing Touch Chakra Connection) or control (Healing Touch Video) group. Self-assessed stress, blood pressure, cortisol, and IL6 were collected before and after the healing touch intervention or control video. The bio-field intervention led to significant decreases in self-reported levels of stress, and stress related biological markers (blood pressure, cortisol, and IL6). Decreases in blood pressure were (statistically) greater for the treatment than for the control but not for the other markers (cortisol and IL6). The higher the level of stress before the intervention, as measured by one of the stress measures, the greater the decrease in stress regardless of treatment group. This study lends support to Principle 5 of the Complex Systems Science and supports bio-field interventions for the treatment of anxiety in university students.